THE EFFECT OF BONDED SOCIAL CAPITAL AND BRIDGING SOCIAL CAPITAL ON ENTREPRENEUR'S PERFORMANCE MODERATED WITH AWARENESS VARIABLES ON OPPORTUNITY AND OPERATIONAL COMPETENCY IN ENTREPRENEURS - Shandio Leo Vandianxo; Dewi Wuisan (Universitas Pelita Harapan, 2022)
This study aims to identify the effect of bound social capital and to bridge social capital on entrepreneurial Performance, which is moderated by the variables Awareness of opportunities and operational competence of entrepreneurs. This research approach uses quantitative methods and data collection methods which are distributed through electronic questionnaires via a google form. This research is aimed at entrepreneurs, with a total of 160 respondents. The instrument used for collecting questionnaire data consists of 24 indicators. Testing the questionnaire was carried out with the reliability test method and validity test, and the tools used to analyze the data using the application smart-PLS 3.2.9. The results of the study explain that bound social capital has a positive effect on entrepreneurial Performance, bridging social capital has a positive effect on entrepreneurial Performance, operational competence does not moderate the positive influence between social capital that is tied to entrepreneurial Performance, operational competence moderates the positive effect of bridging social capital on entrepreneurial Performance, Awareness of opportunities does not moderate the positive influence between social capital that is tied to entrepreneurial Performance, Awareness of opportunities does not moderate the positive influence of social capital that bridges on entrepreneurial Performance.